A molecular theory of large-solute diffusion - Yoshimori, A. (Condensed Matter Physics, 2007)
The limit of a large solute in the molecular theory of diffusion developed by Yamaguchi et al. [Yamaguchi T. et al., J. Chem. Phys., 2005, 123, 034504] is studied. By the limit, the Stokes approximation to the hydrodynamic equations is derived in the outside region of a diffusing solute. The limit of a large solute also leads to equations in the inside region of the solute. The analytical solution of the inside equation allows one to derive the boundary condition, which is needed on the surface of the solute when the hydrodynamic equations are calculated. The boundary condition includes stick and slip boundary conditions employed by the Stokes law, in the special case. Besides stick and slip conditions, other conditions can be expressed. The boundary condition depends on properties of a solvent.